Genpolitisering og postdemokratisering: Studiet af mellemøstlig politik i lyset af de arabiske revolter - Valbjørn, Morten; Boserup, Rasmus Alenius (Politik, 2012)
A prominent theme in the current debate on the implications of the Arab Revolts revolves around the questions about whether we are witnessing the emergence of a truly new Middle East in a ‘transition to de- mocracy’, or whether the region is still stuck in a ‘transition to nowhere’ similar to past decades. Based on a critique of both of these views, the article suggests that the Arab world should instead be perceived as being in a ‘transition to somewhere’ marked by a multi-level repoliticization. Against this background, we explore how this ‘return of politics’ in Arab societies is re ected above, below and beyond the level of the regime and how this can be grasped by an ‘upgraded’ version of the postdemocratization approach to Arab politics.